Karyawan dan Produk (Sebuah Tinjauan MSDM Tour and Travel Haji dan Umroh di Sedati Sidoarjo Perspektif Ekonomi Syariah) - Muhimmah, Fatihatul Firda (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
Discussing the relationship between employees and products in the context of human resource management (HRM) in the Hajj and Umrah tour and travel industry in Sedati, Sidoarjo, with a sharia economic perspective. This study highlights the importance of the role of employees in improving the quality of services and products that are in accordance with sharia principles. Through a sharia economic approach, this study also explores how employees can contribute to creating added value for the company and customer satisfaction. By analyzing employee performance, such as training, motivation, and work environment, it is expected to find effective strategies to increase employee productivity and loyalty. In addition, this study also assesses the products offered according to public perception and market potential in the area, thus providing recommendations for business managers in optimizing human resources and products that are in accordance with sharia principles. This study uses a qualitative method with in-depth interviews and observations to collect data from employees and managers at several travel agents in Sedati. The results of the analysis show that trained and motivated employees have a positive response to the quality of products and services offered. In addition, the application of sharia economic principles in business operations has been shown to increase public trust through the products offered. Recommendations resulting from this study include the development of ongoing training programs, increased incentives for employees, and more effective marketing strategies to attract potential pilgrims.